Revealing the spatial heterogeneity of the gut microbiota of red-feather ducks and their interaction with environmental microorganisms - Surong Zhang; Yun Ye; Boqi Wan; Rui Shao; Yuan Fang; Yuanxiu Wang; Jinyuan Wu; Hui Yang (Poultry Science)
Ducks are one of important economic waterfowl species, and their gastrointestinal microbiota play crucial roles in nutrient metabolism, immune regulation, and host health maintenance. In this study, we collect 436 gastrointestinal content samples from red-feather ducks, including samples from the glandular stomach, muscular stomach, duodenum, ileum and cecum, as well as 10 environmental samples (water and soil). We then employed 16S rRNA gene sequencing to explore the gastrointestinal microbial communities of ducks and their interactions with environmental microbes from soil and water. The gastrointestinal microbial community of red ducks showed a spatial gradient distribution characteristic in a counterclockwise direction from the proximal glandular stomach to the distal cecum. Notably, key taxa such as Helicobacter and Bacteroides were identified as significant drivers of spatial microbial distribution. Furthermore, a random forest analysis revealed that 20 genera, including Helicobacter, Bacteroides, and Candidatus Arthromitus could serve as indicator bacteria for distinguish gastrointestinal segments with an accuracy of 93.18 %. Besides, the cecum exhibited the highest microbial α-diversity compared to other gut regions, with enrichment of some short-chain fatty acid (SCFA)-producing microbes like Bacteroides, Faecalibacterium, and Prevotellaceae_Ga6A1_group. Co-occurrence network analysis demonstrated the ileum exhibited the highest microbial connectivity. β-diversity analysis showed that, in comparison to the soil samples, the microbial composition of water samples exhibited greater similarity to the intestinal microbial community of ducks. Microbial source tracking further revealed that the microbial composition in water was primarily shaped duck gut microbiota, with a contribution rate of up to 72.77 %. These findings elucidated the spatial heterogeneity of gastrointestinal microbiota in red-feather ducks and explored the microbial transmission between the environment and the duck gastrointestinal tract (GIT), thereby establishing a theoretical foundation for comprehending waterfowl gut microbial ecosystem, refining husbandry practices, and enhancing understanding of environmental interactions.